Measurement of purpose in life among Arabic-speaking adolescents: psychometric properties of an Arabic-language version of the Claremont purpose scale (CPS) - Noureddine, Amir; Hallit, Souheil; Malaeb, Diana; Sakr, Fouad; Dabbous, Mariam; Cosgrove, Tylor; Obeid, Sahar; Fekih-Romdhane, Feten; Moustafa, Ahmed A. (Frontiers in Psychology, 2025)
BackgroundPurpose in life is considered a protective factor related to one's ability to thrive, supporting positive development and overall psychological wellbeing of the adolescent. The main goal of our study is to adapt and validate the Claremont purpose scale (CPS) into the Arabic language, expanding its applicability to Arabic-speaking contexts.MethodsData for this cross-sectional study was collected via a Google Form link during November 2023. Lebanese adolescents aged 14 to 18 years (N = 793, 62.4% females, mean age of 16.08 ± 1.74 years) were recruited using an online questionnaire and a snowball sampling technique.ResultsThe fit of the three-factor structure of CPS scores was satisfactory as indicated by the Confirmatory Factor Analysis. Internal reliability was excellent (α = 0.86; ω = 0.87). Measurement invariance across sex groups was established at the metric, configural, and scalar levels. There was no significant difference between male and female respondents in terms of CPS scores. Finally, CPS total scores were significantly correlated with greater depression-happiness (r = 0.43; p < 0.001), higher wellbeing (r = 0.51; p < 0.001), and lower irritability (r = –.66; p < 0.001), attesting to concurrent validity.ConclusionOur results suggest that the CPS in its Arabic version is a valid and reliable measure allowing to detect the sense of purpose in Arabic-speaking adolescents, at least from Lebanon. The new validated scale has potential for future practitioners and researchers who would ought to work on ways of improving the psychological functioning of adolescents drawn from an Arab culture.